UJI PREFERENSI SCAEVA PYRASTRI (DIPTERA: SYRPHIDAE) TERHADAP TANAMAN MIMOSACEAE DAN PAPILIONACEAE BERDASARKAN KETERTARIKANNYA TERHADAP BAU - Gunawan Gunawan (Universitas Lambung Mangkurat, 2005)
To optimalize the existence of natural enemies, it is necessary to provide some plants as microhabitat, alternative foods, place for perching, mating and shelter. This research was done to know the most attractive plant of Mimosaceae (Mimosa pigra and Mimosa pudica) and Papillionaceae (Centrosema pubescens and Crotalaria retusa) for Scaeva pyrastri. In addition, the research can be used to find out the combination of those plants which are examined using olfactometer based on the volatile chemicals released by the plants. Scaeva pyrastri, member of the family Syrphidae, was captured from field. Then, it is aclimazed for 24 hours in laboratory. Fours plants about 21 grams of biomassa are put in the four glass boxes. The insect, Scaeva pyrastri, was put in the centre of olfactometer connected to the glass boxes by the odours arms. The orientation collected from 30 multiplication was analized statistical descriptively. For single test, Scaeva pyrastri was highly attracted to Centrosema pubescens and the orientation time needed was about 1 minute 23 second. For combination test, the most atraccting plant was Centrosema pubescens and the orientation time needed was about 1 minute 15 seconds.